L’éducation et le soin comme agir sur soi : liminaire - Jean-Marie Barbier (Éducation et Socialisation)
In introductory text to this Issue, Jean-Marie Barbier focuses particularly on a common characteristic shared by education and care, while they are seen as a joint construction of activities and of subjects, realized by the activities and in the activities : both fields of practice require inevitably a "coupling" between the activity of a specialist and the activity of the targeted interlocutor, by the desired transformation. This is the most general case for all "societal professions". In the contemporary western context, acting on oneself, acting by oneself and acting for one-self come often from the same culture of action. The ordered actions dominating the transformation of oneself and by oneself involve three conditions : to recognize to be able to act on oneself ; to engage oneself as a subject of one's own transformation ; a space for "self-cultivation".